2010
DOI: 10.1038/jcbfm.2010.62
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the MEK/ERK Pathway with a Raf Inhibitor Prevents Activation of Pro-Inflammatory Mediators in Cerebral Arteries and Reduction in Cerebral Blood Flow after Subarachnoid Hemorrhage in a Rat Model

Abstract: Cerebral ischemia that develops after subarachnoid hemorrhage (SAH) carries high morbidity and mortality. Inflammatory mediators are involved in the development of cerebral ischemia through activation of the mitogen-activated protein kinase pathway. We hypothesized that blockade of the MAPkinase/ERK (MEK)/extracellular signal-regulated kinase (ERK) pathway upstream with a specific raf inhibitor would prevent SAH-induced activation of the cerebrovascular inflammatory response. The raf inhibitor SB-386023-b was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 32 publications
5
68
1
Order By: Relevance
“…However, the authors did not find increased cytokine mRNA levels in the cerebral artery walls after SAH (Maddahi et al, 2011). This suggests that the cytokines in the smooth muscle layer are either synthesized outside the vessels or by a small subpopulation of infiltrating cells in the smooth muscle cell layer, such as leukocytes.…”
Section: The Role Of Inflammation In Cerebrovascular Pathophysiologymentioning
confidence: 89%
See 3 more Smart Citations
“…However, the authors did not find increased cytokine mRNA levels in the cerebral artery walls after SAH (Maddahi et al, 2011). This suggests that the cytokines in the smooth muscle layer are either synthesized outside the vessels or by a small subpopulation of infiltrating cells in the smooth muscle cell layer, such as leukocytes.…”
Section: The Role Of Inflammation In Cerebrovascular Pathophysiologymentioning
confidence: 89%
“…In experimental SAH, the delayed global cerebral ischemia 2 days after the SAH was also shown to be associated with enhanced protein levels of IL-1b, IL-6, and nitric oxide synthase in the smooth muscle layer of cerebral arteries (Maddahi et al, 2011). Blockage of the MEK/ERK pathway prevented this response in both models, and this effect could also be seen when treatment with the blocker was delayed for up to 6 hours after the insult (Maddahi and Edvinsson, 2010;Maddahi et al, 2011).…”
Section: The Role Of Inflammation In Cerebrovascular Pathophysiologymentioning
confidence: 93%
See 2 more Smart Citations
“…Subarachnoid hemorrhage increased iNOS in both wild-type and eNOS KO mice, which is consistent with other studies in wild-type animals. 26,27 Increased iNOS activity could produce more ROS and aggravate brain injury and large artery vasospasm. [28][29][30] Yatsushige et al, 31 however, found that inhibiting the increase in iNOS after SAH in rats did not reduce blood-brain barrier breakdown, brain edema, neuron death, or mortality.…”
Section: Discussionmentioning
confidence: 99%